An evaluation of the generalization and maintenance of functional communication and self‐control skills with preschoolers. Issue 2 (14th May 2014) - Luczynski, Kevin C.; Hanley, Gregory P.; Rodriguez, Nicole M.
<x xml:space="preserve">Abstract</x> The preschool life skills (PLS) program (Hanley, Heal, Tiger, & Ingvarsson, 2007; Luczynski & Hanley, 2013) involves teaching social skills as a means of decreasing and preventing problem behavior. However, achieving durable outcomes as children transition across educational settings depend on the generalization and long‐term maintenance of those skills. The purpose of this study was to evaluate procedures for promoting generalization and long‐term maintenance of functional communication and self‐control skills for 6 preschool children. When the children's social skills decreased across repeated observations during a generalization assessment, we incorporated modifications to the teaching procedures. However, the effects of the modifications were variable across skills and children. Satisfactory generalization was observed only after the teacher was informed of the target skills and teaching strategies. Maintenance of most social skills was observed 3 months after teaching was discontinued. We discuss the importance of improving child and teacher behavior to promote generalization and maintenance of important social skills.